What does it mean to be poor in a rich society? - Haveman, Robert (Madison, 2009)
"The author extends the discussion of poverty and its measurement beyond the current U.S. model that dates to the mid-1960s. He explores European Union and United Kingdom proposals for comprehensive measures that consider indicators of material deprivation and "social exclusion." He concludes with a proposal for developing a measure of poverty and social exclusion for the United States."